Reevaluating the photophysics and electronic structure of Cr(III) and V(II) complexes: the implications of distortion on the excited state manifold - Portillo, Romeo I., author; Shores, Matthew P., advisor; Rappé, Anthony K., committee member; Chen, Eugene Y.-X., committee member; Peterson, Christopher, committee member (Colorado State University. Libraries, 2020)
Presented in this dissertation are investigations into the electronic structure of chromium and vanadium complexes targeted towards photocatalysis. These studies have focused on two primary features in the excited state manifold: the energy of the excited state and the relative distortion of the excited state to the ground state. Chapter 1 provides a background on how the study of electron transfer led to the development of inorganic photocatalysis. The chapter includes the progression of photocatalysts design from [Ru(bpy)3]2+ to modern alternatives focusing on Earth-abundant reagents. Additionally, I provide my perspective on these advances and criticism of prevalent methodologies. Chapter 2 discusses the synthesis and characterization of polypyridyl-containing Cr(III) complexes. Each complex exhibits spectroscopic signatures of an unusual 4(3IL) excited state, a mixed excited state between a paramagnetic ligand and metal center. Calculations provide insight into the character of this excited state, suggesting this 4(3IL) excited state may be the lowest spinallowed excited state in some of these complexes. The minimal distortion in these excited states limit the degrees of freedom for non-radiative decay compared to the metal-based 4T2 excited state. Chapter 3 discusses the synthesis and characterization of two V(II) polypyridyl complexes. Here, I reevaluate the proposed excited state manifold in the literature which claims that the 4MLCT is the lowest energy excited state. Spectroelectrochemical and picosecond-resolved spectroscopic techniques reveal a short-lived excited state, presumably 2MLCT. A new excited state manifold is presented, suggesting doublet excited states are relevant to the understanding of V(II) photophysics. Chapter 4 discusses the differences in the electronic structure of isoelectronic V(II) and Cr(III) polypyridyls. While several factors contribute to these differences, the identity and energies of the relevant excited states lead to a completely different excited state manifold between the two systems. The chapter summarizes the work of Chapters 2 and 3. Chapter 5 discusses the synthesis and electronic structure of a tripodal ligand scaffold bound to V(II) and V(III). The differences between the hexacoordinate V(II) and heptacoordinate V(III) further our understanding of the apical nitrogen's role on the electronics of the complex. Additionally, we exploit the utility of the SHAPE program to quantify structural distortion and correlate to the species' electronic structure. Chapter 6 discusses the electronic structure of a similar vanadium tripodal complex, [V((5-CO2Me)py)3tren]2+ . This complex displays spectroscopic signals of both a V(II) complex with a neutral ligand and V(III) complex with a ligand radical. Different phenomena are proposed, but neither provide a complete explanation of the results. Chapter 7 summarizes the investigations into V(II) and Cr(III) photophysics. Additionally, I discuss how SHAPE may be used in other fields and identify important structural motifs through machine learning.
Keywords: coordination complexes; photochemistry; vanadium; electronic structure; chromium; photophysics